Appling the science of learning to university teaching and beyond - Hakel, Milton D.; Halpern, Diane F. (New York : Jossey - Bass, 2002)
Sus temas principales son: 1.- Learning that lasts a lifetime teaching for long term, 2.- Biologyis to medicine as psychology is to education, 3.- Successful lecturing presenting information in way that, 4.- Improving comprehension through discourse processing, 5.- The theory of successful intelligence as a basis for instruction
Keywords: Pedagogía - Evaluaciones educativas